2013
DOI: 10.3126/njh.v7i1.8500
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension in Semi-Urban area of Nepal

Abstract: Hypertension is one of the major cardiovascular problems in middle and low income countries. There are few studies conducted in Nepal which shows significant number of hypertensive popu­lation in suburban area. Systematic random sampling from voter lists of all the members more than 18 years of age of Dhulikhel Municipality was done. 796 among 1150 sampled population were interviewed and their blood pressure was measured twice using mercury sphygmomanom­eter in standard method in their home. The average blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
6
15
1
Order By: Relevance
“…These associations are well established in various studies conducted at national and international level. 9,10,12,25,[27][28][29][30][31][32][33] Hypertension prevalence increased with advancing age (Table 1) in this study which is consistent with findings from number of other studies. [27][28][29][30][31][32][33] Majority of the respondents (152) in this study were female.…”
Section: -14supporting
confidence: 82%
See 3 more Smart Citations
“…These associations are well established in various studies conducted at national and international level. 9,10,12,25,[27][28][29][30][31][32][33] Hypertension prevalence increased with advancing age (Table 1) in this study which is consistent with findings from number of other studies. [27][28][29][30][31][32][33] Majority of the respondents (152) in this study were female.…”
Section: -14supporting
confidence: 82%
“…9,10,12,25,[27][28][29][30][31][32][33] Hypertension prevalence increased with advancing age (Table 1) in this study which is consistent with findings from number of other studies. [27][28][29][30][31][32][33] Majority of the respondents (152) in this study were female. This may be because, male population were not available at the time of data collection as they were out of the house for their job, while majority of the female population were homemaker, and were available at the time of data collection.…”
Section: -14supporting
confidence: 82%
See 2 more Smart Citations
“…17 Among 215 participants having high blood pressure currently, 80 (37.20%) were not aware that they have high BP. The data is higher in compare to the 7th Report of the JNC on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure which stated it was approximately 30 percent 2 and is much less than a study of Dhulikhel that showed 69.9% of hypertensive were unaware of their hypertensive status 14 and almost similar (39.1%) to a study of city malls in Kathmandu that showed only 39.13%.…”
mentioning
confidence: 99%